2023
DOI: 10.1021/acs.jafc.3c03646
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Benzothiazolylpyrazole-4-Carboxamides as Potent Succinate Dehydrogenase Inhibitors through Active Fragment Exchange and Link Approach

Yan-Ming Yin,
Zong-Yue Sun,
Da-Wei Wang
et al.

Abstract: Succinate dehydrogenase (SDH) is an attractive target for developing green fungicides to manage agricultural pathogens in modern agriculture research. Herein, in this work, we report the discovery of benzothiazolylpyrazole-4-carboxamides I-III as potent SDH inhibitors using active fragment exchange and link approach. The results of the fungicidal activity assays showed that some of the synthesized compounds exhibited excellent inhibition against the tested fungi. Systematic structure−activity relationship stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Herein, in this study, we designed 3-( N -phenyluracil)­but-2-enoates I – IV through active fragments exchange and link (AFEL), an approach developed by us to discover the lead compounds of the enzyme (Figure ). Our results showed that the E -configuration of 3-( N -phenyluracil)­but-2-enoates I – IV showed higher bioactivity than their corresponding Z -configuration analogues. Most of the synthesized E -configuration compounds exhibited higher N.…”
Section: Introductionmentioning
confidence: 65%
“…Herein, in this study, we designed 3-( N -phenyluracil)­but-2-enoates I – IV through active fragments exchange and link (AFEL), an approach developed by us to discover the lead compounds of the enzyme (Figure ). Our results showed that the E -configuration of 3-( N -phenyluracil)­but-2-enoates I – IV showed higher bioactivity than their corresponding Z -configuration analogues. Most of the synthesized E -configuration compounds exhibited higher N.…”
Section: Introductionmentioning
confidence: 65%
“…Yin and colleagues designed and synthesized a new series of compounds containing benzothiazolylpyrazole-4-carboxamides as a potent SDH inhibitor scaffold, using an active fragment exchange and link approach. 54 According to the fungicidal activity assays, some of the synthesized compounds, namely compound 26, exhibited excellent inhibition against the tested fungi (Figure 6d). Compound 26 showed higher fungicidal activity against Fusarium graminearum (F. graminearum) (EC 50 = 0.93 mg•L −1 ) than thifluzamide (EC 50 > 50 mg•L −1 ) and boscalid (EC 50 > 50 mg•L −1 ), which are commercial fungicides.…”
Section: Five-membered Rings (Diazoles) 221 Pyrazole Containing Struc...mentioning
confidence: 98%
“…Yin and colleagues designed and synthesized a new series of compounds containing benzothiazolylpyrazole-4-carboxamides as a potent SDH inhibitor scaffold, using an active fragment exchange and link approach . According to the fungicidal activity assays, some of the synthesized compounds, namely compound 26 , exhibited excellent inhibition against the tested fungi (Figure d).…”
Section: Review Backgroundmentioning
confidence: 99%
“…This type of fungicides has become the next most popular fungicide after quinone outside respiration inhibitors and ergosterol biosynthesis inhibitor fungicides. SDHIs can block the mitochondrial tricarboxylic acid cycle and respiratory chain electron transport [2], thereby exerting its fungicidal activity by inhibiting the activity of succinate dehydrogenase [3]. As of now, there were 24 SDHIs on the fungicide resistance action committee [4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Molecules can be generated based on RNN models [8][9][10]. The generative model based on variational autoencoder (VAE) consists of two networks: (1) encoder, which maps the input into a low-dimensional latent vector; (2) decoder, which maps the latent vector into the newly generated data [11]. Both the encoder and decoder can be common RNN or convolutional neural networks (CNN) models.…”
Section: Introductionmentioning
confidence: 99%